Distribution of ACE2, CD147, CD26, and other SARS‐CoV‐2 associated molecules in tissues and immune cells in health and in asthma, COPD, obesity, hypertension, and COVID‐19 risk factors - Radzikowska, Urszula; Ding, Mei; Tan, Ge; Zhakparov, Damir; Peng, Yaqi; Wawrzyniak, Paulina; Wang, Ming; Li, Shuo; Morita, Hideaki; Altunbulakli, Can; Reiger, Matthias; Neumann, Avidan U.; et al. (Allergy (Copenhagen), 2020)
Background Morbidity and mortality from COVID‐19 caused by novel coronavirus SARS‐CoV‐2 is accelerating worldwide, and novel clinical presentations of COVID‐19 are often reported. The range of human cells and tissues targeted by SARS‐CoV‐2, its potential receptors and associated regulating factors are still largely unknown. The aim of our study was to analyze the expression of known and potential SARS‐CoV‐2 receptors and related molecules in the extensive collection of primary human cells and tissues from healthy subjects of different age and from patients with risk factors and known comorbidities of COVID‐19. Methods We performed RNA sequencing and explored available RNA‐Seq databases to study gene expression and co‐expression of ACE2, CD147 (BSG), and CD26 (DPP4) and their direct and indirect molecular partners in primary human bronchial epithelial cells, bronchial and skin biopsies, bronchoalveolar lavage fluid, whole blood, peripheral blood mononuclear cells (PBMCs), monocytes, neutrophils, DCs, NK cells, ILC1, ILC2, ILC3, CD4+ and CD8+ T cells, B cells, and plasmablasts. We analyzed the material from healthy children and adults, and from adults in relation to their disease or COVID‐19 risk factor status. Results ACE2 and TMPRSS2 were coexpressed at the epithelial sites of the lung and skin, whereas CD147 (BSG), cyclophilins (PPIA andPPIB), CD26 (DPP4), and related molecules were expressed in both epithelium and in immune cells. We also observed a distinct age‐related expression profile of these genes in the PBMCs and T cells from healthy children and adults. Asthma, COPD, hypertension, smoking, obesity, and male gender status generally led to the higher expression of ACE2‐ and CD147‐related genes in the bronchial biopsy, BAL, or blood. Additionally, CD147‐related genes correlated positively with age and BMI. Interestingly, we also observed higher expression of CD147‐related genes in the lesional skin of patients with atopic dermatitis. Conclusions Our data suggest different receptor repertoire potentially involved in the SARS‐CoV‐2 infection at the epithelial barriers and in the immune cells. Altered expression of these receptors related to age, gender, obesity and smoking, as well as with the disease status, might contribute to COVID‐19 morbidity and severity patterns. ACE2 and TMPRSS2 expression is unique for the epithelial barrier sites, whereas CD147, cyclophilins, and CD26 are expressed in both, epithelial and immune cells. Age is a factor associated with the differential expression profiles of ACE2‐, CD147‐ and CD26‐related genes in the PBMCs and naive CD4+ T cells from healthy children and adults. Asthma, COPD, hypertension, smoking, obesity, and male gender generally lead to the higher expression of ACE2‐ and CD147‐related genes in the bronchial biopsy, BAL or blood. Abbreviations: ACE2, angiotensin‐converting enzyme 2; AD, atopic dermatitis; BAL, bronchoalveolar lavage; COPD, chronic obstructive pulmonary disease; CypA, cyclophilin A; CypB, cyclophilin B; GLUT1, glucose transporter 1; ILC, innate lymphoid cell; MCTs, monocarboxylate transporters; NF‐ATs, nuclear factor of activated T cells; PBMCs, peripheral blood mononuclear cells; SARS‐CoV‐2; severe acute respiratory syndrome coronavirus 2; SLC6A19, sodium‐dependent neutral amino acid transporter B(0)AT1; S100A9, protein S100‐A9; TMPRSS2, transmembrane protease serine.